Analysis of the Effect of the Friction Coefficient on a Pavement Structure - Lu Bai; Yong-sheng Zhang (Advances in Materials Science and Engineering)
Insufficient skid resistance of pavement is one of the main causes of traffic accidents. In this study, the influence of the friction coefficient on the internal effect of the pavement structure is studied deeply by establishing the asymmetric finite element numerical model. The model analyzes the inner stress, strain, and displacement variations of the pavement, with friction coefficients under the conditions of 0.3, 0.5, 0.8, and 1.0 and the action of the nonlinear superposition between the single-point static vertical load and horizontal load. In addition, against the limitations of the scatter calculation results, this paper analyzes the distribution of the internal stress field and displacement field. The results show that, with the attenuation of the friction coefficient, the distribution law of stress, strain, and displacement on the road surface (Z = 0) remains unchanged, and the maximum principal strain and the third principal strain on the Z-axis decrease monotonically with increasing depth. With the attenuation of the friction coefficient, the horizontal displacement inside the pavement structure gradually decreases, the vertical displacement changes insignificantly, and the principal stress gradually decreases. The principal strain and maximum shear stress inside the pavement structure show different changing rules.